T2 relaxation times of macromolecules and metabolites in the human brain at 9.4 T. Issue 2 (31st January 2020) - Murali‐Manohar, Saipavitra; Borbath, Tamas; Wright, Andrew Martin; Soher, Brian; Mekle, Ralf; Henning, Anke
Abstract : Purpose: Relaxation times can contribute to spectral assignment. In this study, effective T2 relaxation times ( T 2 eff ) of macromolecules are reported for gray and white matter–rich voxels in the human brain at 9.4 T. The T 2 eff of macromolecules are helpful to understand their behavior and the effect they have on metabolite quantification. Additionally, for absolute quantification of metabolites with magnetic resonance spectroscopy, appropriate T2 values of metabolites must be considered. The T2 relaxation times of metabolites are calculated after accounting for TE/sequence‐specific macromolecular baselines. Methods: Macromolecular and metabolite spectra for a series of TEs were acquired at 9.4 T using double inversion–recovery metabolite‐cycled semi‐LASER and metabolite‐cycled semi‐LASER, respectively. The T2 relaxation times were calculated by fitting the LCModel relative amplitudes of macromolecular peaks and metabolites to a mono‐exponential decay across the TE series. Furthermore, absolute concentrations of metabolites were calculated using the estimated relaxation times and internal water as reference. Results: The T 2 eff of macromolecules are reported, which range from 13 ms to 40 ms, whereas, for metabolites, they range from 40 ms to 110 ms. Both macromolecular and metabolite T2 relaxation times are observed to follow the decreasing trend, with increasing B0 . The linewidths of metabolite singlets can be fully attributed to T2 and B0 components. However, in addition to these components, macromolecule linewidths have contributions from J‐coupling and overlapping resonances. Conclusion: The T2 relaxation times of all macromolecular and metabolite peaks at 9.4 T in vivo are reported for the first time. Metabolite relaxation times were used to calculate the absolute metabolite concentrations.